(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Computational thinking (CT) is often associated with computer science, but its versatility makes it a valuable tool for navigating life in a technology-driven world. CT serves as an essential educational skill, promoting problem-solving, critical thinking, and student engagement across various disciplines. Advanced CT skills help prepare students for the challenges of modern life and contribute to success in both professional and personal spheres. Previous studies show a strong connection between computational thinking and academic achievement, suggesting that developing these skills can enhance overall educational outcomes. The latest findings from the International Association for the Evaluation of Educational Achievement (IEA) International Computer and Information Literacy Study (ICILS) 2023, highlight significant differences in how students develop CT skills, raising important questions about equal access to quality education. This study uses data from ICILS 2023 to examine differences between schools where students excel in CT and those where these skills are less developed. Across nine participating countries, no significant differences were found in access to ICT resources or in teachers’ use of ICT in and outside the classroom. Moreover, no specific curriculum topics stood out as key factors driving high CT performance in certain schools. However, students in top-performing schools were more likely to engage in independent learning on internet-related topics and demonstrated better focus during lessons. These schools also tended to accumulate students from higher socioeconomic backgrounds (SES) and were often located in larger cities or more affluent areas. In some countries, including Latvia, selective admission processes may further contribute to these students' strong performance—not just in CT but across a range of subjects.